Topics in Modal Analysis & Testing, Volume 10 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Mains, Michael (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Topics in Modal Analysis & Testing, Volume 10. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the tenth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: • Modal Analysis, Measurements & Parameter Estimation • Basics of Modal Analysis • Additive Manufacturing & Modal Testing of Printed Parts • Modal Analysis & Model Updating • Modal Testing Methods.